Precise Urea/Water Eutectic Composition by Temperature‐Resolved Second Harmonic Generation. Issue 7 (23rd March 2016) - Yuan, Lina; Clevers, Simon; Couvrat, Nicolas; Cartigny, Yohann; Dupray, Valérie; Coquerel, Gérard
Abstract: The use of temperature‐resolved second harmonic generation (TR‐SHG) to determine the accurate eutectic composition between urea and water is illustrated. The TR‐SHG results were confirmed with differential scanning calorimetry and thermal stage microscopy observations. Due to the sensitivity of this technique, by precisely differentiating the liquidus temperature and the eutectic temperature, the eutectic composition was determined to be between 32.8 and 32.9 wt %, compared to 32.5 wt % for the commercial aqueous urea solution marketed for NOx concentration reduction. This study demonstrates that TR‐SHG is a promising tool for precisely determining the eutectic compositions of binary systems involving at least one non‐centrosymmetric phase. Abstract : The eutectic composition of the urea/water binary system was precisely determined by temperature‐resolved second harmonic generation (TR‐SHG). Around the eutectic composition, the liquidus temperature and the eutectic temperature can be clearly separated by TR‐SHG, revealing SHG to be a sensitive technique for the precise determination of a eutectic composition.